Consumer Protection in The Perspective Of Islamic Law: The Principle of Dignified Justice - Wibowo, Dwi Edi; Disantara, Fradhana Putra (Trunojoyo Madura University, 2024)
Consumer protection in the context of dignified justice does not only prioritize economics and business, but also considers respect for ethics and human values. Consumer protection from an Islamic legal perspective will prioritize the principle of dignified justice as its main basis. Justice in Islamic sharia does not only include fulfilling rights equally, but also regarding respect for human dignity as creatures of God, so that dignified justice in Islam is justice that collaborates moral, spiritual and social values to maintain a balance between rights and obligations. Islamic sharia not only protects consumers from material loss, but will also maintain human dignity as legal subjects, this is because Islam teaches the values of al-'ilah (justice), maslahah (benefit), hisbah (supervision), and their relevance to protection of consumer rights. The principle of dignified justice emphasizes that consumers' rights must be protected and treated with respect, including consumer rights to correct information, freedom from fraud, and guarantees of product quality. This research uses a philosophical normative approach which will discuss the importance of values in Islamic sharia to provide more fair protection for consumers. Therefore, integrating the principles of Islamic law into regulations governing consumer protection can be a strategic step to create dignified justice for all parties.